Impact of deceptive advertising on consumer buying decision on social media with mediating word of mouth: an empirical study from University of Tabuk, Saudi Arabia - Abdulbaqi, Hebatalla Mohsen Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
This paper aims to study impact of deceptive advertising on consumer buying decision on social media with mediating effect of word of mouth, and also aim To find out, what types of deceptive ads practice exists on social media, and what are the most effective practices of advertising deception on the decision-making of students through social media, and To find out the effect of word of mouth on consumer buying decision, and to Providing some guidelines for companies to follow to avoid deceptive advertising Practices. The study was conducted in University of Tabuk in Saudi Arabia, the research hypotheses were adopted based on the previous studies, and Based on variables of the study, the researcher tried to identify the effects of each variable on consumer buying decision. The researcher used the descriptive analytical method; The Data was collected through Field research (questionnaire) among 120 respondents. The results show that there was a positive correlation between deceptive advertising and the buying behavior among university students and also there was positive correlation between advertising deception and word of mouth that affect buying behavior among university students. The study recommended, that the governments should enact a law with all provisions to promote and protect the rights of a consumer and establish authority.